Genetic counselling difficulties and ethical implications of incidental findings from array‐CGH: a 7‐year national survey. Issue 5 (4th January 2016) - Lefebvre, M.; Sanlaville, D.; Marle, N.; Thauvin‐Robinet, C.; Gautier, E.; Chehadeh, S.E.; Mosca‐Boidron, A.‐L.; Thevenon, J.; Edery, P.; Alex‐Cordier, M.‐P.; Till, M.; Lyonnet, S.; et al.
Abstract : Microarray‐based comparative genomic hybridization (aCGH) is commonly used in diagnosing patients with intellectual disability (ID) with or without congenital malformation. Because aCGH interrogates with the whole genome, there is a risk of being confronted with incidental findings (IF). In order to anticipate the ethical issues of IF with the generalization of new genome‐wide analysis technologies, we questioned French clinicians and cytogeneticists about the situations they have faced regarding IF from aCGH. Sixty‐five IF were reported. Forty corresponded to autosomal dominant diseases with incomplete penetrance, 7 to autosomal dominant diseases with complete penetrance, 14 to X‐linked diseases, and 4 were heterozygotes for autosomal recessive diseases with a high prevalence of heterozygotes in the population. Therapeutic/preventive measures or genetic counselling could be argued for all cases except four. These four IF were intentionally not returned to the patients. Clinicians reported difficulties in returning the results in 29% of the cases, mainly when the question of IF had not been anticipated. Indeed, at the time of the investigation, only 48% of the clinicians used consents mentioning the risk of IF. With the emergence of new technologies, there is a need to report such national experiences; they show the importance of pre‐test information on IF. Abstract : Section Editor: Aad Tibben, email:a.tibben@lumc.nl